2023
DOI: 10.3389/fnins.2023.1247021
|View full text |Cite
|
Sign up to set email alerts
|

System-level biological effects of extremely low-frequency electromagnetic fields: an in vivo experimental review

Haoyang Tian,
Haozheng Zhu,
Chenhao Gao
et al.

Abstract: During the past decades, the potential effects of extremely low-frequency electromagnetic fields (ELF-EMFs) on human health have gained great interest all around the world. Though the International Commission on Non-Ionizing Radiation Protection recommended a 100 μT, and then a 200 μT magnetic field limit, the long-term effects of ELF-EMFs on organisms and systems need to be further investigated. It was reported that both electrotherapy and possible effects on human health could be induced under ELF-EM radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Particularly noteworthy is the fact that none of the studies included in this review reported any negative side effects of ELF-MFs. A review of in vivo experiments conducted in 2023 [59] indicated that the majority of studies suggest that exposing patients to ELF-MFs does not result in significant adverse outcomes, thus this therapy method is deemed safe. However, reports presenting undesirable effects of ELF-MFs can be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly noteworthy is the fact that none of the studies included in this review reported any negative side effects of ELF-MFs. A review of in vivo experiments conducted in 2023 [59] indicated that the majority of studies suggest that exposing patients to ELF-MFs does not result in significant adverse outcomes, thus this therapy method is deemed safe. However, reports presenting undesirable effects of ELF-MFs can be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ELF-EMFs have been shown to promote neuronal differentiation through NMDA receptor activation [17]. This suggests that ELF-EMFs could potentially be used to modulate neuronal function and cognitive behaviors [18].…”
Section: Pulsating Elf-emf Exposure and Potential For Nsc Differentia...mentioning
confidence: 99%
“…While the study by Ma et al presents findings that differ from ours, this discrepancy could be attributed to their specific application of ELF-EMFs-a singular strength of 2 mT, 50 Hz for a duration of 3 days. A multitude of studies have indeed demonstrated that the effects observed post-ELF-EMF application are contingent on various parameters such as the frequency, strength, and duration of treatment [18,20]. Given this variability, it is not surprising to encounter contradictory effects.…”
Section: Pulsating Elf-emf Exposure and Potential For Nsc Differentia...mentioning
confidence: 99%
“…Much of the work shows that the main targets of ELF-MFs are the cardiovascular and nervous systems. [118]. The effects of ELF-MFs on the immune, musculoskeletal, and other systems have also been described [119].…”
Section: Effects On the Whole Organism (Laboratory Studies)mentioning
confidence: 99%
“…Historically and recently, biological effects of EFs and MFs were often considered together [118,342,343]. We suppose that the effects of electric (EFs) and magnetic fields (MFs) in this frequency range should be considered separately.…”
Section: Biological Effects Of Extremely-low-frequency Electrical Fieldsmentioning
confidence: 99%